Interview with Amanda Warner, designer of Influence, Inc. - Warner, Amanda (Gamevironments, 2022)
Amanda just released Influence, Inc., her second game about propaganda and media manipulation after her 2017 game Fake It to Make It. In this interview I am learning from her about how the game works in allowing players to explore propaganda, what Amanda's aims with the game are, and how she thinks about games as a medium and their impact on the politics. The interview has been conducted by Patrick Prax over Zoom on the 19th of April 2022, with additions and revisions through subsequent exchanges.